Study on antihepatocellular carcinoma effect of 6-shogaol and curcumin through network-based pharmacological and cellular assay - Jin, Qiuxia; Jiao, Wenya; Lian, Yunhe; Chitrakar, Bimal; Sang, Yaxin; Wang, Xianghong (Frontiers in Pharmacology, 2024)
Background Hepatocellular carcinoma currently has the third highest mortality rate in the world. Patients with hepatocellular carcinoma are on the rise and at a younger age, but research into the pharmacological effects of cancer is mostly single-component, and natural plant products can have additive or synergistic effects that can better amplify the effects of intervention in cancer. Aim To evaluate the synergistic therapeutic effects of 6-shogaol and curcumin against hepatocellular carcinoma line HepG2 cells. Methods In this study, a network pharmacology approach was used to predict and validate the mol ecular targets and pathways of the hepatocellular carcinoma (HCC) of 6-shogaol and curcumin in combination and to investigate their mechanism of action. The results were also validated by cellular assays. HepG2 cells were treated with 6-shogaol and curcumin as well as the combination of the two. The combination index of 6-shogaol and curcumin in HepG2 cells was calculated using Compusyn software according to the Chou-Talalay equation. The synergistic anti-cancer effect was next investigated by MTT assay, apoptosis assay and cell cycle assay. The combined anti-hepatocellular carcinoma effect of the Ras-mediated PI3K/AKT and MAPK signalling pathways was analysed using protein blotting assays. Results A network pharmacology-based screening identified 72 core targets of 6-curcumin and curcumin in hepatocellular carcinoma, and predicted that the main signalling pathway is the Ras signalling pathway. The anti-cancer effects of 6-shogaol and curcumin were validated in cell-based assays and the optimal synergistic concentrations of 5 μmoL/L for 6-shogaol and 30 μmoL/L for curcumin were determined. 6-shogaol and curcumin synergistically blocked the cell cycle in the G2/M phase and promoted apoptosis. Immunoblot analysis confirmed for the first time the combined action of both in down-regulating the Ras-mediated PI3K/AKT and MAPK signaling pathways. In addition, 6-shogaol and curcumin acting together downregulated Cyclin-B, CDK-1, Bcl-2, and upregulated BAX. Conclusion 6-shogaol and curcumin act synergistically to alter the morphology of hepatocellular carcinoma cells, block the cell cycle in the G2/M phase, inhibit proliferation and division, and effectively promote late apoptosis. The combined action of these two components provides a theoretical basis for the further development of novel anti-liver cancer products.